Measuring the timing ability and performance of bond mutual funds☆ - Chen, Yong; Ferson, Wayne; Peters, Helen (Journal of Financial Economics, 2010)
This paper evaluates the ability of bond funds to “market time” nine common factors related to bond markets. Timing ability generates nonlinearity in fund returns as a function of common factors, but there are several non-timing-related sources of nonlinearity. Controlling for the non-timing-related nonlinearity is important. Funds’ returns are more concave than benchmark returns, and this would appear as poor timing ability in naive models. With controls, the timing coefficients appear neutral to weakly positive. Adjusting for nonlinearity, the performance of many bond funds is significantly negative on an after-cost basis, but significantly positive on a before-cost basis.